Effects of Cognitive‐, Social‐, and Group‐Awareness Tools on Learners' Cognitive Load in Computer‐Mediated Writing Classes. - Chen, Shunmeng (Journal of Computer Assisted Learning, 2025)
Background: Computer‐mediated writing classes have experienced a significant increase in popularity in recent years, serving as an effective modality for enhancing writing skills within an online framework. Objectives: This study seeks to bridge the gap in the literature by investigating the effectiveness of cognitive, social, and group‐awareness tools in reducing cognitive load in this context. Methods: This investigation employed a pretest‐posttest randomised experimental design to scrutinise the influence of awareness tools (cognitive, social, and group) on cognitive load management and computer‐mediated writing performance among 144 EFL learners. Descriptive statistics and ANOVA were utilised to process the data. Results: The outcomes demonstrated no statistically significant disparities in computer‐mediated writing performance scores between the experimental and control groups during the pretest phase. However, in the posttest phase, the control group displayed markedly higher scores in comparison to the experimental groups that were exposed to cognitive, social, and group awareness tools. Importantly, the social and group awareness tools positively impacted writing performance scores. Conclusions: The results suggest that incorporating social and group‐awareness tools into computer‐mediated writing activities may contribute to elevated writing performance among EFL learners. Consequently, teachers and instructional designers should contemplate implementing group activities and collaboration tools within computer‐mediated writing tasks to cultivate the social and collaborative aspects of writing.